(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Women everywhere across the world crave for equal treatment and equal rights as that of their male counterparts. Misogyny is prevalent among human beings from centuries and hence, feminism as a discourse seeking a conscious individual identity for women, has flourished to give voice to the unheard, unnoticed, and exploited part of the human race - women. As a movement, feminism has served incalculable women in the history of humankind in numerous ways. Women through different expressions explain the complex scenario of suppression by patriarchal authorization. Women are imprisoned in their sex which itself does impose on her certain limitations. Male patriarchy is a socio-cultural phenomenon from the very birth of a kid, irrespective of sex, the socio-cultural hammering begins and deforms the psyche of an individual forever. Women were viewed as objects in the 14th century with the increasing popularity of “nude” paintings. The thesis on Women’s Poetic Responses to the Male Gaze Cutting Them Down by Nadine Yonka justifies that those paintings “in 14th century” were usually painted by men with their objects being beautiful, “naked, passively positioned women”. In Ways of Seeing, Berger says that “men look at women. Women watch themselves being looked at”, and describes male painters’ psychology while painting a woman, the “person who is the object of their [male painters’] activities – woman – is treated as a thing or an abstraction”. And more than this, “the ‘ideal’ spectator is always assumed to be male and the image of the woman is designed to flatter him” In this Article, we tried to understand The Feminism in Islamic and African Literature.